TINJAUAN NERACA MASSA PADA PROSES PENGOMPOSAN TANDAN KOSONG KELAPA SAWIT DENGAN PENAMBAHAN AIR LIMBAH PABRIK KELAPA SAWIT [A Review of Mass Balances in Composting Process of Empty Fruit Bunches by Addition of Palm Oil Mill Effluent] - Ribut Sugiharto; Erdi Suroso; Budi Dermawan (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2016)
The waste generated from oil palm mills in the form of empty fruit bunches (EFB) and palm oil mill effluent (POME) can be used utilized to be processed into compost, which is beneficial for treating waste from palm oil mills as well as generate organic fertilizer that can be applied to land. The research was conducted to determine the mass balance in the form of input and output during the compost production process and carried out in a pilot scale in order to give an idea if composting is done on a large scale. This research aimed to analyze the mass balance of composting process of EFB and POME and calculate C/N ratio of EFB and compost, respectively. The research was conducted in a descriptive experimental method and data were presented in tables and graphs. The composting is carried out in two replications and without treatment. The composting was carried out for 54 days, during the research, temperature, pH and water content were monitored. The results showed that the maximum temperature during the composting process were 49.9 to 50.90 °C, the pH value were 6.85 to 7.94, the water content during were 76.81 to 77.88%. Overall, the input as EFB and POME were 34.91 to 37.33% and POME 62.67 to 65.09%, respectively. The Output in form of leachate and compost were about 27.02 to 27.58%, and 24.04 to 26.09%, respectively, and evaporated materials were about 46.33 to 48.94%. For composing, 1.0 ton EFB required POME about 1.57 to 1.74 m3, produced compost about 688.62 to 698.85 kg, leachate about 0.724 to 0.758 m3 (density = 1.02 kg/dm3), and evaporated material about 1241.26 to 1401.95 Kg. The C/N ratio on EFB was 28.86 and C/N ratio of the compost was 8.91.Keywords: empty fruit bunches, mass balance, palm oil mill effluent